2014
DOI: 10.1111/pim.12144
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of recombinant antigens of Trypanosoma cruzi to diagnose infection in naturally infected dogs from Chaco region, Argentina

Abstract: Dogs are considered the main mammal reservoir of Trypanosoma cruzi in domiciliary environments. Consequently, accurate detection of T. cruzi infection in canine populations is epidemiologically relevant. Here, we analysed the utility of the T. cruzi recombinant antigens FRA, SAPA, CP1, Ag1 and a SAPA/TSSA VI mixture, in an ELISA format. We used a positive control group of sera obtained from 38 dogs from the Chaco region in Argentina with positive homogenate-ELISA reaction, all of them also positive by xenodiag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…We also demonstrate that Chagas Sero K -SeT is applicable, without modification, to dogs. In two previous studies on T. cruzi lineage-specific serology in Argentine dogs [12, 22], recombinant TSSA-II/V/VI protein was only used in ELISA. As with humans, we found that there was concordance between ELISA and Chagas Sero K -SeT RDT, and that a greater number of T. cruzi seropositive samples tested by both methods were positive with the RDT, confirming the greater sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also demonstrate that Chagas Sero K -SeT is applicable, without modification, to dogs. In two previous studies on T. cruzi lineage-specific serology in Argentine dogs [12, 22], recombinant TSSA-II/V/VI protein was only used in ELISA. As with humans, we found that there was concordance between ELISA and Chagas Sero K -SeT RDT, and that a greater number of T. cruzi seropositive samples tested by both methods were positive with the RDT, confirming the greater sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…At the same site a distinct amino acid sequence is shared by TcII/V/VI, and the hybrids TcV/VI also have a second sequence, as they are heterozygous and have two haplotypes at that locus [10]. Recombinant TSSA produced in E. coli or synthetic peptide epitopes (TSSApep) have been used with Argentine chagasic samples for T. cruzi lineage-specific serology [9, 1121], particularly with the isoform common to TcII/V/VI; the recombinant form has also been used for canine serology [12, 22].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the latter point, the application of serology based on lineage-specific antigens has great potential for resolving the cryptic ecological cycles and the discovery of novel reservoir hosts of this parasite. Applications of T. cruzi lineage-specific serology to naturally-infected animals are with dogs [17,26], primates [18] and sympatric dogs, cats, and armadillo [20]. We have applied Chagas Sero K-SeT to exploit the capacity of Protein G to recognise TSSApep-II/V/VI specific IgG from a range of mammalian Orders.…”
Section: Discussionmentioning
confidence: 99%
“…Rocha et al [13] genotyped TcII from Brazilian dogs, as single or mixed TcI-TcII infections in Minas Gerais State, southern Brazil. Previous reports [17,26] have used a recombinant E. coli-produced TSSA fusion protein from CL Brener strain (TcVI; a clone from parental strain CL) in ELISA with naturally infected dogs from northern Argentina; however, the recombinant included sequences that are shared with other lineages. Chagas Sero K-SeT identified TcII/V/VI infections in dogs from Ceará state, in north-eastern Brazil, a region previously known to be highly endemic for TcII in domestic transmission cycles, although intradomiciliary transmission of T. cruzi has now been controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Availability of gTSSA-I serology enables parallel investigation of clinical status associated with TcI infection, and serological detection of sporadic TcII/V/VI and TcI co-infections, which occur in some Bolivian and Brazilian endemic foci 40 , 41 . As with application of TSSA-II/V/VI serology to sylvatic mammals 20 , 21 , 23 , 42 , 43 , gTSSA-I can be deployed for resolution of TcI domestic and sylvatic transmission cycles, and for discovery of reservoir hosts. Thus, expression of L. tarentolae recombinant antigens representing epitopes specific to each of the T. cruzi lineages, may facilitate comprehensive epidemiological investigations.…”
Section: Discussionmentioning
confidence: 99%